2021
DOI: 10.1111/jch.14310
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure variability and cognitive dysfunction: A systematic review and meta‐analysis of longitudinal cohort studies

Abstract: The variability of blood pressure (BPV) has been suggested as a clinical indicator for cognitive dysfunction, yet the results from clinical studies are variable. This study investigated the relationship between BPV and the risk of cognitive decline or dementia. Bibliographic databases, including PubMed, Scopus, and Embase, were searched systematically for longitudinal cohort studies with BPV measurements and neuropsychological examinations or dementia diagnosis. A traditional meta‐analysis with subgroup analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“…The findings are complicated regarding the influence of BPV on cognitive function at different life stages. For example, some studies indicated the relationship between BPV and cognitive impairment in the aged population over 60 years old [4,6,[24][25][26][27][31][32][36][37]45]. For example, one large systematic review with twenty cohort studies of around eight million persons found the effect of SBPV on all-cause dementia was more prominent among the older age (>65 years) [45].…”
Section: Age Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings are complicated regarding the influence of BPV on cognitive function at different life stages. For example, some studies indicated the relationship between BPV and cognitive impairment in the aged population over 60 years old [4,6,[24][25][26][27][31][32][36][37]45]. For example, one large systematic review with twenty cohort studies of around eight million persons found the effect of SBPV on all-cause dementia was more prominent among the older age (>65 years) [45].…”
Section: Age Differencesmentioning
confidence: 99%
“…For example, some studies indicated the relationship between BPV and cognitive impairment in the aged population over 60 years old [4,6,[24][25][26][27][31][32][36][37]45]. For example, one large systematic review with twenty cohort studies of around eight million persons found the effect of SBPV on all-cause dementia was more prominent among the older age (>65 years) [45]. In addition, exaggerated ambulatory BPV was associated with cognitive dysfunction in the elderly, especially in the very elderly (!80 years old) and lower quality of life in the younger elderly (61-79 years old) [37].…”
Section: Age Differencesmentioning
confidence: 99%
“…2 The registered review question was "What is the difference between long-term and short-term blood pressure variability (BPV) in relation with cognitive decline or incidence of dementia regarding general population or specific subgroup? 2 " Concerningly, the discrepancy between the review's main aim and that of the published version 1 was not addressed, nor was a PRISMA checklist 3 provided with this paper, 1 which specifies for authors to describe any changes from the protocol (item 24c of PRISMA checklist 3 ). Moreover, in the published version, 1 it is clear the meta-analysis was unable to sufficiently answer the review question, 2 with only one study identified for mid-term BPV, and three or less studies analyzed for long-term BPV.…”
Section: Live Long and Prospero: A Comment On Chiu And Coworkersmentioning
confidence: 99%
“…To begin with, we would like to address the inherent limitation of the observational study, which is the type of research included into our systematic review and meta‐analysis. 1 Due to the inability of randomization and, for some, retrospective design, the conventional analysis of the observational studies (eg, calculating odds ratio or hazard ratio) can only infer correlation instead of causation. Techniques such as causal inference have been developed to determine causality from observational studies, yet in our meta‐analysis, the effect estimates we extracted and synthesized are associative in nature.…”
mentioning
confidence: 99%